Application of prehabilitation program in elderly patients undergoing esophageal cancer surgery - Zhou, Kun; Cai, Fengjuan; Shao, Xiao; Luo, Caifeng; Liu, Zihao (Frontiers in Oncology, 2025)
ObjectiveTo explore the effectiveness of prehabilitation program on elderly patients undergoing esophageal cancer surgery.MethodsA total of 96 elderly esophageal cancer surgery patients from a tertiary hospital were selected. The control group included 48 patients treated from August to November 2023, and the prehabilitation group consisted of 48 patients treated from December 2023 to March 2024. The control group received routine care from the time of diagnosis until surgery, while the prehabilitation group received the prehabilitation program in addition to routine care. The nutritional status, hospital anxiety and depression scale (HADS), six-minute walking distance (6MWD), and quality of life (SF-36) were compared between the two groups at different time points before and after the intervention. Additionally, postoperative hospital stay, time to chest drain removal, time to first ambulation, and complications were evaluated.ResultsDuring the research process, in the control group, one case fell out, while two cases fell out in the prehabilitation group. The t-test and Mann Whitney U test showed that at different time points after the intervention, the indicators in the prehabilitation group were significantly better than those in the control group (P<0.05), although there was no significant difference in complications (P>0.05). Repeated measures ANOVA indicated that there were interaction effects, intervention effects, and time effects on HADS, 6MWD, and SF-36 scores at each time point in both groups (P<0.05).ConclusionPrehabilitation has a positive effect on improving the functional reserve, nutritional status, and psychological well-being of elderly patients undergoing esophageal cancer surgery, thus promoting postoperative recovery.